PENGARUH PEMBERIAN BUPIVACAINE DOSIS 0,5 % 15 mg DAN 20 mg TERHADAP PENURUNAN TEKANAN SISTOL PADA TINDAKAN URETEROSCOPIC LITHOTRIPSY DENGAN SPINAL ANASTESI: Waelan, Amin Zakaria, Sindu Sintara, Widigdo Rekso Negoro - Waelan waelan; Amin Zakaria; Sindu Sintara; Widigdo Rekso Negoro (Jurnal Kesehatan Hesti Wira Sakti, 2023)
Decreased blood pressure, is one of the problems that often occurs during URS procedures with spinal anesthesia, although not always significantly. Therefore, it is very important to choose the right dose of bupivacaine so that unwanted side effects can be minimized, (American Society of Anesthesiologists., 2021). Bupivacaine 0.5% doses of 15 mg and doses of 20 mg are often used to provide anesthesia, but it is still unclear whether higher doses provide significant clinical benefits or actually increase the risk of side effects, (Wang, L. Z., at. all., 2015 ). The purpose of this study was to analyze the effect of giving a dose of 0.5% bupivacaine 15 mg and 20 mg on reducing systolic pressure in ureteroscopic procedures with spinal anesthesia. This study can provide important information regarding therapeutic doses, so that postoperative follow-up care related to the risk of lowering blood pressure can be minimized. Methods: The study design was an analytic observational prospective cohort design, looking at the differences in the observed results between the two groups given injections of 0.5% bupivacaine doses: 15 mg and 20 mg. The population, namely patients who underwent URS procedures with spinal anesthesia, totaled 60 respondents who were divided into two groups: the first 30 respondents were given a dose of 15 mg and the second dose was 20 mg. The research was carried out in the operating room at the Army Hospital Level II Malang within one month of research. Independent variable: administration of 0.5% bupivacaine injection at a dose of 15 mg and 20 mg and dependent variable: decrease in systolic blood pressure in URS patients with spinal anesthesia. Using the Biocare Patient Monitor Model iM 15 instrument and recorded on the observation sheet, which was carried out before being given the local anesthetic drug bupivacaine 0.5% and after giving anesthesia in the first 5 minutes, 10 minutes and 15 minutes. Bivariate data analysis, namely by using the Independent T-Test Different Test was processed with the help of a computer using the SPSS series 22 application. Results: Injection of 5% bupivacaine doses with 15 mg and 20 mg had the same effect on reducing systolic blood pressure in URS with spinal procedures anesthesia, the decrease in blood pressure was within normal limits. There was no significant difference in the average systolic blood pressure reduction values, namely 13.13 mmHg and 15.3 mmHg so that the difference in the average value was only 1.87 mmHg and the significance values ​​were p values ​​0.000 and 0.001. This is because the use of doses is still within the safe limits recommended by pharmaceutical manufacturers, the systolic blood pressure measurement time carried out by researchers is up to 15 minutes after injection of bupivacaine which should be up to 40 minutes after injection. Suggestion: Injection of a dose of 5% bupivacaine with 15 mg and 20 mg in the URS procedure with spinal anesthesia is still effective for use and for future researchers the minimum time to measure blood pressure is up to 40 minutes after the injection is carried out.